Total Colonic Tubular Duplication Associated With Anorectal Malformation: A Case Report and Surgical Reconstruction Approach - Dhon Rizal Gusnanda; Ismar Ismar; Tubagus Odih Rhomdani Wahid; Khairuli Amri; Andrea Valentino; Sinta Chaira Maulanisa (Jurnal Ners, 2026)
Total colonic duplication is an exceptionally rare subtype of gastrointestinal duplication, often associated with anorectal malformations. Diagnostic difficulty arises from variable morphology, shared mesenteric structures, and inconsistent imaging findings. Early recognition remains limited, and many cases are identified only during operative exploration. A 10-month-old male with a history of anorectal malformation previously treated with colostomy underwent evaluation for definitive repair. Intraoperative assessment, including loop colonography, identified two parallel colonic lumens extending from cecum to rectum. Exploratory laparotomy confirmed complete tubular duplication with a shared mesentery. Reconstruction was achieved through a side-to-side window anastomosis using a stapling device, followed by creation of a protective ileostomy. Postoperative recovery was uneventful, with adequate stoma perfusion and preserved bowel function. The patient remained stable during follow-up and was scheduled for staged abdominoperineal anoplasty. Complete colonic duplication may not be detected preoperatively and frequently requires intraoperative confirmation. Preservation of vascular supply and staged reconstruction are central to optimizing outcomes.Individualized surgical planning and careful anatomical delineation support favorable early recovery and functional prognosis in total colonic duplication with anorectal malformation.